2018
DOI: 10.1002/ajb2.1178
|View full text |Cite
|
Sign up to set email alerts
|

Monocot plastid phylogenomics, timeline, net rates of species diversification, the power of multi‐gene analyses, and a functional model for the origin of monocots

Abstract: We present the first plastome phylogeny encompassing all 77 monocot families, estimate branch support, and infer monocot-wide divergence times and rates of species diversification. METHODS:We conducted maximum likelihood analyses of phylogeny and BAMM studies of diversification rates based on 77 plastid genes across 545 monocots and 22 outgroups. We quantified how branch support and ascertainment vary with gene number, branch length, and branch depth.KEY RESULTS: Phylogenomic analyses shift the placement of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
233
5
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 188 publications
(276 citation statements)
references
References 155 publications
32
233
5
6
Order By: Relevance
“…The concatenated supermatrix alignment was comprised of 16 loci with 32,925 base pairs. Phylogenetic relationships agree with our current understanding of the monocot phylogeny (Givnish et al, ; Howard et al, ); however, we recover age estimates across the tree that vary in the degree of congruence with past studies (Figure ), likely due to our widespread taxon sampling and/or age estimation methodology. Fortunately, PGLS analyses are robust to phylogenetic uncertainty (e.g., branch lengths; Díaz‐Uriarte & Garland, ; Stone, ), and thus, we included the phylogeny simply as a correction for the remaining post‐tree analyses.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The concatenated supermatrix alignment was comprised of 16 loci with 32,925 base pairs. Phylogenetic relationships agree with our current understanding of the monocot phylogeny (Givnish et al, ; Howard et al, ); however, we recover age estimates across the tree that vary in the degree of congruence with past studies (Figure ), likely due to our widespread taxon sampling and/or age estimation methodology. Fortunately, PGLS analyses are robust to phylogenetic uncertainty (e.g., branch lengths; Díaz‐Uriarte & Garland, ; Stone, ), and thus, we included the phylogeny simply as a correction for the remaining post‐tree analyses.…”
Section: Resultssupporting
confidence: 83%
“…Time calibration was performed using penalized likelihood as implemented in treePL (Smith & O'Meara, ). The following calibration points were as follows: (a) a fossil dated between 48.88 and 49.96 MYA at the crown of Amaryllidaceae (Pigg, Bryan, & DeVore, ), (b) a fossil dated between 33.8 and 34 MYA placed at the crown of Alismataceae (Iles, Smith, Gandolfo, & Graham, ), (c) a fossil dated between 72.1 and 83.6 MYA placed at the crown of Zingiberales (Iles et al, ), (d) a fossil dated at 23.2 MYA at the crown of Asteliaceae, (e) a fossil dated between 14.5 and 16.2 MYA at the crown of Agavoideae, (f) a secondary calibration of 133–136 MYA at the split between Acorus calamus and the remaining monocots (Givnish et al, ), and (g) a secondary calibration of 136–139.35 MYA at the split between Amborella trichopoda and the remaining angiosperms (Magallón, Gómez‐Acevedo, Sánchez‐Reyes, & Hernández‐Hernández, ). One priming step followed by 10 cross‐validations was performed in order to obtain the appropriate smoothing parameter of 0.1.…”
Section: Methodsmentioning
confidence: 99%
“…In this scenario, the evolution of a rhizome may have required the further development (or loss) of anatomical and physiological changes (e.g., the vascular cambium). More recently, using a phylogenomic approach, it has been found that the ancestral state of the monocots was likely a submerged aquatic and/or amphibious, herbaceous plant (Givnish et al., ). Our findings complement this hypothesis; on the basis of extant variation in monocots, it is likely that such an aquatic ancestor exhibited a rhizomatous growth form.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings complement this hypothesis; on the basis of extant variation in monocots, it is likely that such an aquatic ancestor exhibited a rhizomatous growth form. The advantages of the mobile habit afforded by a rhizome would allow individuals to efficiently regulate both water and soil depth, thus, improving gas exchange (Givnish et al., ). Perhaps, populations were pre‐adapted for a changing climate by possessing buds on belowground rhizomes that crept along the water's edge.…”
Section: Discussionmentioning
confidence: 99%
“…Nymphaeales, Nelumbo, Ceratophyllum, and Podostemaceae are all aquatic lineages (60). Even in the case of monocots, the last common ancestor of the lineage has been proposed to have been semiaquatic (61). Although there are many types of aquatic habits, submersion in or proximity to water means that aquatic plants typically do not require extensive mechanical reinforcement or high fluid transport capacity.…”
Section: Discussionmentioning
confidence: 99%